Bacterial Cross‐contamination Potential Associated with Contaminated Currency. Issue 6 (19th August 2016) - Kesavan, Jana; Stephens, Amelia; Kesavan, Meera
Abstract: Previous studies have shown a significant amount of contaminants on paper currencies. It is important to study the transfer of microorganisms between paper currencies to determine whether it meets the level of a human health threat. This cross‐contamination potential was analyzed by seeding new US 1‐dollar bills with Bacillus thuringiensis, and pressing or rubbing them against clean currency to determine the amount of bacteria transfer to the unseeded currency. The transferred amount of bacteria was recovered, plated, incubated, and the colony‐forming units were quantified. Among the recovery methods tested, the most efficient method, vortexing for 10 min with a recovery efficiency of 40 ± 8.1%, was used in this analysis. The resulting transfer rates were 4.8%, 8.6%, and 14.3% when pressed for 24 h, 72 h, and rubbed together, respectively. These transferred amounts of bacteria are significant and have the potential to spread infectious diseases.